MỘT SỐ KẾT QUẢ BAN ĐẦU XÁC ĐỊNH HỆ SỐ THẤM BẰNG THÍ NGHIỆM NHANH SLUG TEST TẠI NAM ĐỊNH - Lê, Trần Thành; Nhân, Phạm Quý; Tâm, Vũ Thanh (Vietnam Journal of Earth Sciences, 2012)
Quickly determine of the hydraulic conductivity of the aquifer in Nam Dinh by slug testSlug test was conducted in 23 boreholes of the groundwater monitoring network of the project “Improvement of Groundwater Protection in Viet Nam - IGPVN” and in 12 boreholes of the national groundwater monitoring network in the territory of Nam Dinh Province. The test allows to quickly determine in-situ hydrogeological parameters. The resulting hydraulic conductivity (K) obtained from the slug tests are comparable with those obtained from previous single-well test and core sample grain-size interpretation. The slug test shows that it can be applied in hydrogeological practice in order to reduce the cost of hydrogeological investigation works in Vietnam.